2014
DOI: 10.1186/1471-2407-14-490
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of using serum YKL-40 and SCCA in combination for the diagnosis of patients with esophageal squamous cell carcinoma

Abstract: BackgroundElevated serum YKL-40 levels have been observed in various cancers. We evaluated the diagnostic performance of serum YKL-40 alone or in combination with the CEA, CYFRA21-1 and SCCA tumor markers for patients with esophageal squamous cell carcinoma (ESCC).MethodsYKL-40 was detected in ESCC cell lines and tissues by real-time RT-PCR, Western blotting and ELISA. YKL-40 protein expression was determined in 20 ESCC tumor tissues using immunohistochemistry. Serum YKL-40 was measured by ELISA in 126 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 34 publications
2
35
0
3
Order By: Relevance
“…The retrospective nature of the study and inability to take blood samples for measurements of serum YKL-40 levels made it impossible to check the potential correlation between tissue expression and serum level of this protein. The other studies on squamous cell carcinomas of head, neck and esophagus mentioned above showed elevated serum level of this protein; however, their authors did not find any correlation between the YKL-40 tissue expression and its serum level (24).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The retrospective nature of the study and inability to take blood samples for measurements of serum YKL-40 levels made it impossible to check the potential correlation between tissue expression and serum level of this protein. The other studies on squamous cell carcinomas of head, neck and esophagus mentioned above showed elevated serum level of this protein; however, their authors did not find any correlation between the YKL-40 tissue expression and its serum level (24).…”
Section: Discussionmentioning
confidence: 65%
“…A positive IHC reaction was also observed in inflammatory cells present in tumor stroma. A similarly designed study on esophageal squamous cell carcinoma was conducted (24). In this report positive immunohistochemical reaction was observed in 17 (85%) out of 20 samples of the cancer tissues, with varying strength of reaction (low, medium and high).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Elevated levels of serum YKL-40 were reported to be associated with several types of cancer, such as ovarian, esophageal, breast, lung, liver and kidney cancer (11)(12)(13)(14)(15)(16). Furthermore, high expression of YKL-40 is associated with tumor grade, poor differentiation and shorter overall survival times, and may be a potential biomarker (5,11,13).…”
Section: Discussionmentioning
confidence: 99%